Tailoring Zeolite ZSM‐5 Crystal Morphology/Porosity through Flexible Utilization of Silicalite‐1 Seeds as Templates: Unusual Crystallization Pathways in a Heterogeneous System. Issue 21 (13th April 2016) - Zhang, Hongbin; Zhao, Yang; Zhang, Hongxia; Wang, Peicheng; Shi, Zhangping; Mao, Jianjiang; Zhang, Yahong; Tang, Yi
Abstract: Diffusion limitation in micropores of zeolites leads to a demand for optimization of zeolite morphology and/or porosity. However, tailoring crystallization processes to realize targeted morphology/porosity is a major challenge in zeolite synthesis. On the basis of previous work on the salt‐aided, seed‐induced route, the template effect of seeds on the formation of micropores, mesopores and even macropores was further explored to selectively achieve desired hierarchical architectures. By carefully investigating the crystallization processes of two typical samples with distinct crystal morphologies, namely, 1) nanocrystallite‐oriented self‐assembled ZSM‐5 zeolite and 2) enriched intracrystal mesoporous ZSM‐5 zeolite, a detailed mechanism is proposed to clarify the role of silicalite‐1 seeds in the formation of diverse morphologies in a salt‐rich heterogeneous system, combined with the transformation of seed‐embedded aluminosilicate gel. On the basis of these conclusions, the morphologies/porosities of products were precisely tailored by deliberately adjusting the synthesis parameters (KF/Si, tetrapropylammonium bromide/Si and H2 O/Si ratios and type of organic template) to regulate the kinetics of seed dissolution and seed‐induced recrystallization. This work may not only provide a practical route to control zeolite crystallization for tailoring crystal morphology, but also expands the knowledge of crystal growth mechanisms in a heterogeneous system. Abstract : Seeding diverse morphologies : A salt‐aided, seed‐induced approach was used to tailor ZSM‐5 crystallization. Detailed crystal‐growth features, involving evolution of seeds and transformation of gel, were related to specific synthesis parameters, such as KF/Si, TPABr/Si and H2 O/Si ratios and type of SDA (see figure). This efficient alternative method to selectively tune zeolite morphology and the corresponding crystallization behavior also expands our knowledge of crystal‐growth mechanisms in heterogeneous systems. SDA: structure‐directing agent, TPABr: tetrapropylammonium bromide.